PENGEMBANGAN BAHAN AJAR DIGITAL MENGGUNAKAN HEYZINE FLIPBOOK PADA MATERI INDONESIAKU KAYA RAYA - Nunu Nadia Dwi Rahmawanti; Griet Helena Laihad; Nurlinda Safitri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research uses the type of research RnD (Research and Development). The purpose of this study was to develop and feasibility of digital teaching materials using Heyzine flipbook Indonesiaku Kaya Raya. The subjects of this study were students of class V-A SDN Tanah Sareal 4 Bogor City using ADDIE (Analysis, Design, Development, Implementation, Evaluation). The results of the media expert validity test obtained a percentage of 99%, material experts 92%, and language experts 100%. The response results from students obtained a percentage of 91% and teachers obtained a percentage of 95%. Therefore, the results of the development of digital teaching materials using Heyzine flipbook on Indonesiaku Kaya Raya are declared "Very Feasible" and "Very Good" to be used in the learning process.